EFEKTIVITAS PELAKSANAAN PEMBELAJARAN ONLINE SAAT PANDEMI COVID-19 PADA HASIL BELAJAR SISWA SD: ANALISIS REVIEW - Fransiska Rahmawati; Ahmad Sudi Pratikno (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
The effectiveness of the implementation of online learning during the covid-19 pandemic on the learning outcomes of elementary school students. This research was conducted to determine the effectiveness of the implementation of online learning on the learning outcomes of elementary school students during the covid-19 pandemic. Researchers used Google Scholar and Sinta databases to obtain articles that were used as literature reviews. The research method is carried out by searching using keywords that match the themes and strategies used by the PICOS framework in the database. The implementation of online learning for elementary school students is still foreign to parents, teachers, and students. Online learning activities carried out in their respective homes make elementary school students closer to the use of gadgets so that parents feel worried about their child's development in using technology. Teacher preparation in carrying out online learning requires time in preparing interactive materials and videos so that students are able to clearly understand the material provided. The results of research conducted from various review articles that the implementation of online learning in elementary schools has not been fully effective. This ineffectiveness is because there are still many obstacles in mastering IT, lack of student understanding, network constraints, teacher difficulties in assessing psychomotor and affective students, and internet costs incurred by parents for online learning. Based on a survey conducted by previous researchers, parents of students prefer offline learning to online learning.